Friday

April 18, 2014

April 18, 2014

Posted by **Olivia** on Monday, March 11, 2013 at 1:35am.

Find the average rate of change from 1 to 3

Using f(x) = -2x^2+6x

- Math -
**Henry**, Wednesday, March 13, 2013 at 4:12pmF(x) = -2x^2 + 6x.

F(1) = -2*1^2 + 6*1 = -2 + 6 = 4.

F(3) = -2*3^2 + 6*3 = -18 + 18 = 0.

F(3)-F(1) = 0 - 4 = -4 = Average rate of change.

**Related Questions**

Math - find the average rate of change from 1 to x Find the average rate of ...

calculus - Find the average rate of change f(x)=x^3-8x+9 a. from -3 to -2 b. ...

calculus (rate of change) - consider the function f(x)=x^2-6x+12 a. find the ...

---college algebra (average rate of change)--- - Find the average rate of change...

math - Let f be defined as follows. y=f(x)=x^2-12x (a) Find the average rate of ...

math - Let f be defined as follows. y = f(x) = x^2 - 4 x (a) Find the average ...

---college algebra (average rate of change)--- - If the average rate of change ...

Calculus - for f(x)=-x^2 +1, which value is the largest magnitude? a) average ...

math(rate of change) - find the average rate of change f(x)=x^2 + 2x between x=0...

Calulus - Consider the following function. f(t) = 3t2 − 3 (a) Find the ...